The cost of smile: how individual and organizational factors moderate the impact of emotional labor on work alienation via burnout - Üngüren, Engin; Tekin, Ömer Akgün; Avsallı, Hüseyin (Frontiers in Psychology, 2025)
IntroductionIn the tourism industry, frontline employees are exposed to intense customer interactions that require emotional labor. It is critically important to understand the effects of surface acting and deep acting strategies—performed within the framework of organizational display rules—on adverse psychological consequences such as burnout and work alienation. Building on the Conservation of Resources (COR) and Job Demands–Resources (JD-R) theories, this study examines the mechanisms and boundary conditions of this negative cycle. This study examines an integrated model examining the mediating role of burnout in the relationship between emotional labor strategies (surface and deep acting) and work alienation, and the moderating (buffering) roles of service orientation (as a personal resource) and managerial support (as an organizational resource) in this process.MethodData were collected through random sampling from 1,252 employees working in five-star hotels located in the Alanya and Manavgat regions of Türkiye and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM).ResultsThe findings revealed that surface acting significantly increased both burnout and work alienation, whereas deep acting significantly mitigated these adverse outcomes. Burnout was identified as a partial mediator in the relationship between emotional labor strategies and work alienation. A key finding was the significant buffering effect of both service orientation and managerial support on the relationship between emotional labor and burnout. These resources substantially weakened the positive effect of surface acting on burnout, thereby reducing its detrimental consequences.DiscussionThe results demonstrate that the negative psychological costs of emotional labor can be effectively managed through individual and organizational resources. Theoretically, integrating multi-level resources within a unified model provides a more nuanced understanding for the emotional labor literature. Practically, the findings suggest that hospitality organizations should prioritize selecting service-oriented individuals during recruitment and invest in training programs that foster supportive leadership behaviors among managers.